Testing the Theory of Consumer Discrimination as an Explanation for the Lack of Minority Hiring in Hollywood Films - Kuppuswamy, Venkat; Younkin, Peter (Management Science, 2020)
The underrepresentation of minorities in cultural industries is a widely publicized problem with far-reaching economic and social significance. It is also one of many industries in which employers suggest that the locus of bias is not within the organization but with the consumer. The empirical challenge of relating consumer behavior to employee composition has constrained prior efforts to test their claim and to test the theory of consumer discrimination more broadly. As a result, employers have gradually expanded the scope of the customer discrimination theory from one rooted in direct interaction to include an aversion to simply seeing employees of a different ethnicity. We explore how consumers respond to employee composition by evaluating the performance of films released in the United States as a function of the racial diversity of their cast. We find that films with a single black actor do not differ from those with zero black actors, and that films with multiple black actors in the principal cast actually achieve significantly higher domestic box-office revenues than either. To distinguish between competing explanations for this result, we conduct a vignette-based experiment that allows us to identify a positive influence of diversity on consumers’ assessments of quality, controlling for differences in film or actor appeal. Collectively, these results help discredit one rationale for unequal hiring in cultural industries and also suggest an important qualification to the theory of consumer discrimination: in settings where employee race is visible but the consumer is physically distant, diversity is more profitable than costly. This paper was accepted by Greta Hsu, organizations.